Timing of dietary switching by savannah elephants in relation to crop consumption. (September 2020) - Vogel, Susanne Marieke; Blumenthal, Scott A.; de Boer, Willem Frederik; Masake, Moses; Newton, Ian; Songhurst, Anna Catherine; McCulloch, Graham; Stronza, Amanda; Henley, Michelle Deborah; Coulson, Tim
Abstract: Tree and grass quality on the African savannah shows seasonal variation, driving mixed-feeding herbivores to switch between browsing and grazing. During this switch, crop consumption could be an attractive alternative to browsing. We analysed elephant diet variability in the Okavango Delta, Botswana, using faecal stable isotope ratios of carbon ( δ ^13C) and frequencies of elephant crop consumption, to determine the extent to which crop consumption relates to this potential switch. Although elephants did increase their relative grass consumption in the wet season, browse dominated the annual diet. After February, the proportion of grass in the diet dropped considerably, and continued decreasing through April when farmers reported most crop consumption. Generalized Linear Models revealed that the occurrence of elephant crop consumption increased with the proportion of grass consumed and with decreasing grass quality. The proportion of grass in elephant faeces increased with increasing crop consumption intensity. As crop consumption could also be related to nutrient deficiencies in elephant diet, we calculated the total dietary input of nutrients to reveal potential deficiencies. Elephant diet contained insufficient levels of sodium year-round, and insufficient phosphorus from February to July. As the latter coincides with the timing of crop consumption, we consider our results an indication that phosphorus –and potentially sodium - deficiencies, could play a role in elephant dietary choices, including crop consuming behaviour. Further experimental research is required to show whether supplying elephants with supplementary phosphorus and sodium sources could reduce this micro-nutrient deficiency, and could play a role in reducing elephant crop consumption.